Filtering and Control for Classes of Two-Dimensional Systems - Wu, Ligang (Springer, 2015)
This book focuses on filtering, control and model-reduction problems for two-dimensional (2-D) systems with imperfect information. The time-delayed 2-D systems covered have system parameters subject to uncertain, stochastic and parameter-varying changes. After an initial introduction of 2-D systems and the ideas of linear repetitive processes, the text is divided into two parts detailing: · General theory and methods of analysis and optimal synthesis for 2-D systems; and · Application of the general theory to the particular case of differential/discrete linear repetitive processes.